2014
DOI: 10.1002/2013gl058438
|View full text |Cite
|
Sign up to set email alerts
|

Prompt energization of relativistic and highly relativistic electrons during a substorm interval: Van Allen Probes observations

Abstract: On 17 March 2013, a large magnetic storm significantly depleted the multi-MeV radiation belt. We present multi-instrument observations from the Van Allen Probes spacecraft Radiation Belt Storm Probe A and Radiation Belt Storm Probe B at~6 Re in the midnight sector magnetosphere and from ground-based ionospheric sensors during a substorm dipolarization followed by rapid reenergization of multi-MeV electrons. A 50% increase in magnetic field magnitude occurred simultaneously with dramatic increases in 100 keV el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
124
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 98 publications
(126 citation statements)
references
References 29 publications
2
124
0
Order By: Relevance
“…This event was detected by different space weather dedicated satellites such as the Van Allen Probes which monitor the electron particle dynamics in the Earth's radiation belt. From these data, it appears that the plasmapause boundary was forced deeply inward within the magnetosphere implying high aurora electrojet index and a recovery phase of the storm on March 18 at 03:00 UTC (Foster et al 2014;Baker et al 2014;Boyd et al 2014) which is concordant with ROB-TEC observations.…”
Section: Discussionsupporting
confidence: 79%
“…This event was detected by different space weather dedicated satellites such as the Van Allen Probes which monitor the electron particle dynamics in the Earth's radiation belt. From these data, it appears that the plasmapause boundary was forced deeply inward within the magnetosphere implying high aurora electrojet index and a recovery phase of the storm on March 18 at 03:00 UTC (Foster et al 2014;Baker et al 2014;Boyd et al 2014) which is concordant with ROB-TEC observations.…”
Section: Discussionsupporting
confidence: 79%
“…Assuming that the wave spectrum is wide enough and the wave intensity is sufficiently low, one can model the wave-particle resonant interactions using quasi-linear theory [4][5][6][7] generalized for systems with inhomogeneous magnetic field and background plasma [8,9]. However, various recent spacecraft observations in the near-Earth plasma environment [10][11][12][13][14], laboratory experiments [15,16], and inertial confinement fusion simulations and experiments [17][18][19] have demonstrated that the applicability of quasi-linear theory is often questionable, because electrons happen to interact with coherent waves sufficiently intense to significantly influence electron motion over long time intervals. There are two main effects of such nonlinear wave-particle interactions: particle trapping by the waves (phase trapping) and particle scattering (phase bunching) with nonzero average change of particle energy [20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…The Van Allen Probes satellites, with their 5.5 R E apogee, were well positioned to observe the plume in-situ, and found good agreement with the TEC maps. Additionally, it was found that the plume was oxygen rich: the O + /H + density ratio increased threefold within the plume (Foster et al 2014a). …”
Section: Plasmaphere Transportmentioning
confidence: 99%